2.40. Rozwiąż nierówności: a) 5x * (x – 7) – 2(x ^ 2 + 1) <= (1 - 3x)(6 - x) b) 1 - (1 - x)(- x - 1) - 2x > 6 – x c) – 2(7x – 4) * (x – 7) <= 1 + 7(7 - 2x ^ 2) d) - 4(x + 2) * (1 + x) > 2(1 – 2x ^ 2) 2(1 – 3x) * (4 – x) + 3(x + 5) * (1 – 2x) + 50x <= 0 f) 4x * (6 - x) + (4x - 1)(x - 3) - 2, 5(6 - 4x) < 0 e) g) 1 - (x + 7)(3 + 2x) + 3(x - 5) * (4 + x) <= x ^ 2 h) 2x * (13 - 4x) - (3x - 1)(1 - 2x) + 0, 5(4x ^ 2 + 10) >= 13

2.40. Rozwiąż nierówności: a) 5x * (x – 7) – 2(x ^ 2 + 1) <= (1 – 3x)(6 – x) b) 1 – (1 – x)(- x – 1) – 2x > 6 – x c) – 2(7x – 4) * (x – 7) <= 1 + 7(7 – 2x ^ 2) d) – 4(x + 2) * (1 + x) > 2(1 – 2x ^ 2) 2(1 – 3x) * (4 – x) + 3(x + 5) * (1 – 2x) + 50x <= 0 f) 4x * (6 – x) + (4x – 1)(x – 3) – 2, 5(6 – 4x) < 0 e) g) 1 – (x + 7)(3 + 2x) + 3(x – 5) * (4 + x) <= x ^ 2 h) 2x * (13 – 4x) – (3x – 1)(1 – 2x) + 0, 5(4x ^ 2 + 10) >= 13